MARKETING ASPECTS IN THE SYSTEM FOR PROVIDING ECONOMIC SECURITY OF BUSINESS - SAVCHENKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The research focuses attention on issues and leading aspects of ensuring the economic security of economic entities, but from the point of view of marketing management of the relevant processes. That is why the purpose of the study is to substantiate the marketing aspects in the system of ensuring the economic security of business. Marketing aspects in the system of managing economic security of business naturally relate to two areas: (1) challenges, risks and threats that develop in the marketing system of the business entity; (2) measures and means that have a marketing nature and the implementation of which is aimed at strengthening the economic security of the enterprise. The key challenges facing domestic enterprises and related to the mutual influence of the processes of marketing activity and ensuring the economic security of business arise and develop at the junction of the processes of quality marketing management and the rational implementation of the leading functions of business management in general: planning, organization, analysis , motivation and control. The use of the potential of marketing in ensuring the processes of strengthening the economic security of business lies in the actions organized within the basic components of the marketing mix. Such circumstances increasingly actualize the problem of substantiating theoretical and methodological provisions and applied recommendations regarding the development and application of more progressive mechanisms and tools of marketing policy in order to strengthen not only the competitive, but also the security positions of domestic business entities. Among them, taking into account the current trends of global digitalization, the formation and development of Internet marketing systems of enterprises takes almost the leading position in importance. The tasks of the policy of strengthening the economic security of the business according to the leading components of the marketing mix are defined, namely: product - guaranteeing a high level of the marketing component of the economic security of the enterprise; prevention of trends in lowering the level of its competitiveness; guarantee of consistently high product quality; prevention of complaints; introduction of product innovations; anticipating the appearance on the market of new innovative products, changes in intellectual property; market - preventing market trends from overtaking business sustainability; constant adaptation to changing market conditions; active work on the formation of new markets; price - prevention of increase in the level of consumption; implementation of pricing exclusively on the basis of pricing strategies; prevention of miscalculations in pricing; sales promotion – prevention of miscalculations in advertising campaigns, budgeting of advertising expenses and sales promotion; application of digital methods of competition and dissemination of information about products; forming the foundations of cyber security.